Comparative analysis of autophagy and tauopathy related markers in cerebral ischemia and Alzheimer’s disease animal models - Villamil-Ortiz, Javier G.; Cardona-Gomez, Gloria P. (Frontiers in Aging Neuroscience, 2015)
Alzheimer´s disease (AD) and cerebral ischemia (CI) are neuropathologies that are characterized by aggregates of tau protein, a hallmark of cognitive disorder and dementia. Protein accumulation can be induced by autophagic failure. Autophagy is a metabolic pathway involved in the homeostatic recycling of cellular components. However, the role of autophagy in those tauopathies remains unclear. In this study, we performed a comparative analysis to identify autophagy related markers in tauopathy generated by AD and CI during short-term, intermediate, and long-term progression using the 3xTg-AD mouse model (aged 6,12, and 18 months) and the global CI 2-VO (2-Vessel Occlusion) rat model (1,15, and 30 days post-ischemia). Our findings confirmed neuronal loss and hyperphosphorylated tau aggregation in the somatosensory cortex (SS-Cx) of the 3xTg-AD mice in the late stage (aged 18 months), which was supported by a failure in autophagy. These results were in contrast to those obtained in the SS-Cx of the CI rats, in which we detected neuronal loss and tauopathy at 1 and 15 days post-ischemia, and this phenomenon was reversed at 30 days. We proposed that this phenomenon was associated with autophagy induction in the late stage, since the data showed a decrease in p-mTOR activity, an association of Beclin-1 and Vps34, a progressive reduction in PHF-1, an increase in LC3B puncta and autophago-lysosomes formation were observed. Furthermore, the survival pathways remained unaffected. Together, our comparative study suggest that autophagy could ameliorates tauopathy in CI but not in AD, suggesting a differential temporal approach to the induction of neuroprotection and the prevention of neurodegeneration.